EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, AND EARNINGS MANAGEMENT ON FIRM PERFORMANCE OF PUBLICLY LISTED INDONESIAN COMPANIES IN INDONESIA STOCK EXCHANGE - Magda Ekawiguna, Sylvia
Earnings are an important indicator of financial performance so managers sometimes find themselves under pressure to attain earnings to meet certain objectives. Therefore, in practice, managers exercise discretion without breaking generally accepted accounting principles (GAAP) to make earnings appear greater or lesser than it should be. Firms that are socially responsible would be viewed to be less inclined to manage earnings. Under such a scheme, corporate social responsibility (CSR) and good corporate governance are used as a defense mechanism in the perspective of earnings manipulation. The research aims to obtain a causal relationship among earnings management (EM), corporate social responsibility (CSR), corporate governance (CG), and firm performance (FP).